Let the Evidence Speak Using Bayesian Thinking in Law, Medicine, Ecology and Other Areas - Jessop, Alan (Springer International Publishing, 2018)
This book presents the most important ideas behind Bayes' Rule in a form suitable for the general reader. It is written without formulae because they are not necessary; the ability to add and multiply is all that is needed. As well as showing in full the application of Bayes' Rule to some quantitatively simple, though not trivial, examples, the book also convincingly demonstrates that some familiarity with Bayes' Rule is helpful in thinking about how best to structure one's thinking.